NS encodes an auxin transporter that regulates the 'numerous spines' trait in cucumber (Cucumis sativus) fruit. (17th March 2022) - Liu, Xiaoping; Yang, Xueyong; Xie, Qing; Miao, Han; Bo, Kailiang; Dong, Shaoyun; Xin, Tongxu; Gu, Xingfang; Sun, Jiaqiang; Zhang, Shengping
SUMMARY: Fruit spine is an important agronomic trait in cucumber and the "numerous spines (ns)" cucumber varieties are popular in Europe and West Asia. Although the classical genetic locus of ns was reported more than two decades ago, the NS gene has not been cloned yet. In this study, nine genetic loci for the different densities of fruit spines were identified by a genome‐wide association study. Among the nine loci, fsdG2.1 was closely associated with the classical genetic locus ns, which harbors a candidate gene Csa2G264590 . Overexpression of Csa2G264590 resulted in lower fruit spine density, and the knockout mutant generated by CRISPR/Cas9 displayed an increased spine density, demonstrating that the Csa2G264590 gene is NS . NS is specifically expressed in the fruit peel and spine. Genetic analysis showed that NS regulates fruit spine development independently of the tuberculate gene, Tu, which regulates spine development on tubercules; the cucumber glabrous mutants csgl1 and csgl3 are epistatic to ns . Furthermore, we found that auxin levels in the fruit peel and spine were significantly lower in the knockout mutant ns‐cr . Moreover, RNA‐sequencing showed that the plant hormone signal transduction pathway was enriched. Notably, most of the auxin responsive Aux/IAA family genes were downregulated in ns‐cr . Haplotype analysis showed that the non‐functional haplotype of NS exists exclusively in the Eurasian cucumber backgrounds. Taken together, the cloning of NS gene provides new insights into the regulatory network of fruit spine development. Significance Statement: We demonstrate that NS gene controls numerous spine traits in cucumber. The cucumber glabrous mutants csgl1 and csgl3 are epistatic to ns . NS regulates fruit spine development independently of the tuberculate gene Tu . Moreover, we found that auxin represses the formation of fruit spine in cucumber. Taken together, the cloning of NS gene provides new insights into the regulatory network of fruit spine development.